Studies on Homalomeneae (Araceae) of Borneo IV: Homalomena specimens in the Herbarium Beccarianum-Malesia (FI-B) of the Museo di Storia Naturale—Sezione Botanica “F. Parlatore” dell'Università di Firenze - Peter C., Boyce; Sin Yeng, Wong (Taylor & Francis Ltd., 2009)
Homalomena specimens in the Herbarium Beccarianum-Malesia (FI-B) of the Museo di Storia Naturale dell'Università di Firenze have been examined, and determined. The collection comprises 33 sheets, and one line drawing, of which 16 sheets and the line drawing, representing seven species, originate from Borneo. Eleven type specimens, are represented. Ten types, representing five names (Homalomena beccariana Engl., H. ovata Engl., H. punctulata Engl., H. pygmaea var. latifolia Engl., and H. subcordata Engl.) are pertinent to Borneo.